Il futuro della lettura ad alta voce Alcuni risultati della ricerca educativa internazionale - Batini, Federico (Storie per le persone e le comunità, 2022)
This book originated from the need to review the results and methods of empirical research on reading aloud, and it proposes the translation into Italian of five studies conducted in different parts of the world. The studies were chosen to be representative of different orientations and survey methods, as well as prestigious international peer-reviewed journals with open access. The aim, well-illustrated in the introductory essay by Federico Batini, is to encourage teachers, scholars and decision-makers in our country to attribute a fundamental role to the teaching of reading aloud throughout the entire education path. This should apply not only to children, on whom educational actions and research activities have already tried to focus for several decades. The future of reading aloud, if observed from the particular point of view of international research, seems to promise an intensification of surveys and a broadening of the field of educational application to school age in response to a greater awareness of the effects of reading exposure.